2014
DOI: 10.1089/jmf.2013.2999
|View full text |Cite
|
Sign up to set email alerts
|

Coriander Leaf Extract Exerts Antioxidant Activity and Protects Against UVB-Induced Photoaging of Skin by Regulation of Procollagen Type I and MMP-1 Expression

Abstract: Ultraviolet (UV) radiation causes photodamage to the skin, which, in turn, leads to depletion of the dermal extracellular matrix and chronic alterations in skin structure. Skin wrinkles are associated with collagen synthesis and matrix metalloproteinase-1 (MMP-1) activity. Coriandrum sativum L. (coriander leaf, cilantro; CS) has been used as a herbal medicine for the treatment of diabetes, hyperlipidemia, liver disease, and cancer. In this study, we examined whether CS ethanol extract (CSE) has protective effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 36 publications
(40 reference statements)
1
45
0
2
Order By: Relevance
“…In photoaging skin, expression levels of type I procollagen and MMPs are regulated by the MAPK/AP‐1 signaling pathways . In addition, UVB exposure activates MMP‐1 overexpression, a pivotal enzyme in type I collagen degradation, which accelerates the rate of skin senility . In our study, UVB‐induced phosphorylation of AP‐1 and MAPK was prominently suppressed by treatment with ginsenoside C‐Y to NHDF cells.…”
Section: Discussionmentioning
confidence: 47%
“…In photoaging skin, expression levels of type I procollagen and MMPs are regulated by the MAPK/AP‐1 signaling pathways . In addition, UVB exposure activates MMP‐1 overexpression, a pivotal enzyme in type I collagen degradation, which accelerates the rate of skin senility . In our study, UVB‐induced phosphorylation of AP‐1 and MAPK was prominently suppressed by treatment with ginsenoside C‐Y to NHDF cells.…”
Section: Discussionmentioning
confidence: 47%
“…CSE-treated mice had thinner epidermal layers and denser dermal collagen fibers than untreated mice. On a molecular level, it was further confirmed that CSE-treated mice had lower MMP-1 levels and higher procollagen type I levels than untreated mice [169].…”
Section: Dermatological Effectmentioning
confidence: 76%
“…The mechanisms of the skin that lead to photoaging are induced mainly by the repetitive absorption of UV radiation, which can generate reactive oxygen species and stimulate the expression of extracellular matrix proteases via AP-1 signaling [29]. AP-1, made of Jun and Fos family proteins, is a transcription factor that inhibits collagen production and upregulates collagen breakdown by activating enzymes called MMPs [30].…”
Section: Discussionmentioning
confidence: 99%
“…Because the skin's natural antioxidant defenses are disrupted by high doses of UV light, reactive oxygen species are considered to be key factors involved in the initiation of the skin aging process [23]. Our previous studies demonstrated that Aloe vera , coriander, azuki beans, and Galla chinensis , all of which have antioxidant activity, have protective effects against UVB-induced skin aging [23], [29], [31], [32]. There have been many studies elucidating the antioxidant activities of P. ginseng and C. pinnatifida .…”
Section: Discussionmentioning
confidence: 99%